Trends in Cell Signaling Pathways in Neuronal Fate Decision - Wislet-Gendebien, Sabine (IntechOpen, 2013)
During the last decades, numerous studies about stem cells and regenerative medicine highlighted new therapeutic approaches to treat several neurological disorders. It is noteworthy that the current optimism over potential stem cell therapies is driven by new understandings of stem cell biology leading to specific cell fate decision. The objectives of this book were: 1) to offer a general understanding of signaling pathways underlying the capacity of differentiation of several types of stem cells into neurons, during the development; 2) to understand how those pathways are altered in pathological conditions; 3) to describe advances in cellular therapy that could be use to restore central nervous system dysfunction in pathological conditions.